Perilaku Keagamaan Santri Lanjut Usia(LANSIA) di Pondok Pesantren Sepuh Masjid Agung Payaman Magelang - Imam Machdali; Mangun Budiyanto (Unisia, 2014)
This article aims to study the religious behavior of elderly studentsin Islamic boardingschool of Sepuh Payaman Magelang. analysis in this study is through the fivedimensions; religious belief (ideological), religious practice (ritualistic), religious knowledge (intellectual), religious appreciation (experiential), and experience religion (consequential). The results of this study showed that the ideological dimension embodied in the belief of the pillars of faith in the form of full submission to God as the One single, unified set of all creatures on lafadz tahlil "laa ilaha illa Allah". Second, ritualistic dimension embodied in the practice of religious activities both mahdloh and ghairu mahdlah. Third, Intellectual manifests in learning activities and assessment of students using the book of al-ibriz li Ma'rifah Tafsir al-Qur'an al-Aziz by KH. Bisri Mustafa. The method of the study is "eavesdrop" or listening carefully. Various activities undertaken by the elderly students is serveas a provisioninthe hereafter. Fourth, experiential dimensions embodied in belief and consciousness that hereafter is is the goal of this life. Fifth,consequential dimension manifests in elderly students that all daily activities are alwayssupervised by God and recorded by the angels.